تقييم وتطوير شبكة النقل الداخلي في مدينة اللاذقية وفق مؤشرات الأداء المرورية والنوعية - رستم أكرم; سليمان هبه (Latakia University Journal -Engineering Sciences Series, 2019)
Most of Syrian cities, Latakia city, in particular, suffer from poor transport organizing and Serving of people so that travelling has become a great suffering for most people. After studying the transport situation and the questionnaire that has been written to determine the level of user satisfaction, we found that this city suffers from transport problems like other cities. This is because of transport poor management and regulation including timing, the number of vehicles available and inability to meet demand, which causes a deterioration in the quality of service as a result of traffic congestion and delay. The research provided a comprehensive method to evaluate the performance of public transport network in the city with the ten routes of buses, by evaluating travel time, journey speed, buses volume and frequency, and waiting time, considering these indicators as a criterion for evaluating the performance of public transport, which are related by users’ satisfaction about the network routes, because they are the most effective factors regarding the quality of performance of public transport and improve this performance in future. The research includes a field and practical study of the network elements, routes, buses and stops, by relating the collected engineering and traffic data with survey of users’ satisfaction, that distributed them on random passengers, to find out their opinions about the situation of the public network and evaluate it, to define the problems that they suffer from. Then the data has been inserted into SPSS Statistics Base program and get the level of user satisfaction about the performance indicators of public transport network. The research has concluded that the performance of public transport in Latakia is generally weak and the largest proportion of passengers need to wait a lot of time because it’s very expensive in compare of taxis or minibuses, which do not satisfy the required accessibility to the centre and outskirts of the city, the absence of stops with good conditions and protect the passengers, increases their suffering, and to make the travel process with the wanted level, we suggested a range of recommendations according by local conditions which will reduce the travel problems and raise the transportation performance level. تعاني معظم المدن السورية وخصوصاً محافظة اللاذقية من سوء تنظيم شبكة النقل الداخلي، وبالتالي تخديم الركاب لدرجة أضحى بها التنقل مسبباً معاناة كبيرة لأغلب المواطنين، حيث تبين لنا بعد الاستقصاء الميداني والاستبيان، الذي تمت صياغته لقياس درجة رضا الركاب أن واقع النقل في مدينة اللاذقية يعاني الكثير من المشاكل كغيرها من المدن، وذلك لسوء التسيير والتنظيم الذي يسود قطاع النقل في التوقيت وأعداد وسائل النقل المتاحة وقصورها في تلبية الطلب، مما يتسبب في تقليص جودة الخدمة نتيجة الازدحام والتأخير والكلفة الغير مباشرة. قدم البحث طريقة شاملة لتقييم أداء شبكة النقل الداخلي في المدينة المؤلفة من عشرة مسارات موزعة على أرجاء المدينة، من خلال تحديد وقياس كل من زمن الرحلة وسرعتها، بالإضافة إلى تواتر الباصات وعددها، كما تم قياس أزمنة الانتظار، واعتبار هذه المؤشرات معيار لتقييم أداء النقل العام لارتباطها برضا الركاب المستخدمين لخطوط الشبكة، وكونها أكثر العوامل التي تؤثر على تقييم نوعية أداء النقل العام وتساعد في العمل مستقبلاً على تحسين هذا الأداء. يضم البحث دراسة حقلية وعملية لعناصر الشبكة من مسارات، وسائل نقل ومواقف، وذلك بربط البيانات الهندسية والمرورية المقاسة مع استبيانات رضا للركاب تم توزيعها على عينات عشوائية منهم، تساعد على معرفة آرائهم حول وضع النقل العام في المدينة وتقييمه وفقاً لوجهة نظر المستخدمين، الذين حددوا المشاكل التي يعانون منها، وتم تفريغ الاستبيانات باستخدام البرنامج الإحصائي SPSS Statistics Base والحصول على درجة رضا المستخدمين عن كل مؤشر من مؤشرات أداء الشبكة. توصلت نتائج البحث إلى أن أداء النقل العام في اللاذقية يعتبر غير كافٍ بشكل عام، وأن النسبة الأكبر من الركاب تضطر إلى الانتظار في تنقلاتها وذلك لكلفته الزهيدة مقارنة بالتنقل بالتكاسي، أو مقارنة بالميكروباصات التي لا تؤمن إمكانية وصول جيدة لمواقع في مركز المدينة وأطرافها، كما أن غياب وجود مواقف تؤمن الظروف الملائمة وتحمي الركاب وتخفف عنهم وطأة الانتظار زاد من المعاناة، ولجعل عملية النقل بالمستوى المطلوب اقترحنا مجموعة من التوصيات وفقاً للظروف المحلية بإمكانها أن تخفف من أعباء التنقل وتحسن من أداء الشبكة.